Late Paleozoic Petrified Trees of the Bohemian Paradise - An Insight into the Tropical Forest in Central Europe - Václav Mencl; Radek Mikuláš; Blanka Nedvědická (Geoconservation Research, 2021)
The late Paleozoic deposits in several basins of the Bohemian Massif are well known for their rich abundance of petrified tree trunks. The area of the UNESCO Global Geopark Bohemian Paradise includes a substantial part of one of the largest ones, the Krkonoše Piedmont Basin. Deposits of this basin contain the most complete fossil record of petrified flora among all other coeval basins within the Czech Republic, and petrified stems are known from several stratigraphic levels. Well-preserved anatomical structures allow us to recognize various types of silicified plants. Recent studies identify calamitalean, fern, and various gymnosperm stems, as well as some other plant tissues inside petrified cherts. This paper provides a summary of research on petrified stems from the area and possibilities to use it for tourist and educational activities.